2014
DOI: 10.1186/1750-9378-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Implication of human herpesviruses in oncogenesis through immune evasion and supression

Abstract: All human herpesviruses (HHVs) have been implicated in immune system evasion and suppression. Moreover, two HHV family members, i.e. EBV and KSHV, are recognised as oncogenic viruses. Our literature review summarises additional examples of possible oncogenic mechanisms that have been attributed to other HHVs. In general, HHVs affect almost every cancer-implicated branch of the immune system, namely tumour-promoting inflammation, immune evasion, and immunosuppression. Some HHVs accomplish these effects by inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 75 publications
1
43
0
Order By: Relevance
“…It has been reported that constitutive activation of STAT6 is widely associated with tumor development, including virus-associated cancers (13,15,16,33,34). KSHV, a recently discovered oncogenic herpesvirus, has been shown to escape host immune surveillance through modulating the JAK-STAT pathway (35,36). However, the specific molecular mechanism through which signal pathway modulation occurs remains largely uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that constitutive activation of STAT6 is widely associated with tumor development, including virus-associated cancers (13,15,16,33,34). KSHV, a recently discovered oncogenic herpesvirus, has been shown to escape host immune surveillance through modulating the JAK-STAT pathway (35,36). However, the specific molecular mechanism through which signal pathway modulation occurs remains largely uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…In the latent state, herpesviruses express only a small number of proteins essential for suppressing the host immune system (2). HHVs have evolved various mechanisms for host immune evasion including inhibition of cellular senescence and apoptosis as well as promoting cell proliferation (3). Another strategy to evade host immune surveillance is through expression of viral homologues of genes that are the host's first line of defense against viral infection such as interferons and interferon regulatory factors (IRFs) and therefore sabotage the function and regulation of the cellular proteins (4).…”
mentioning
confidence: 99%
“…Another strategy to evade host immune surveillance is through expression of viral homologues of genes that are the host's first line of defense against viral infection such as interferons and interferon regulatory factors (IRFs) and therefore sabotage the function and regulation of the cellular proteins (4). Deregulation of cellular proteins involved in growth control by HHVs has led to recognition of some HHVs as underlying agents of cancer (3,5).…”
mentioning
confidence: 99%
“…One of the main factors contributing to the successful lifelong persistence of KSHV is its astounding ability to hide from host immune surveillance. During the course of evolution, KSHV has evolved multiple mechanisms to evade and modulate nearly all aspects of both the innate and adaptive immunities of infected hosts (5)(6)(7).…”
mentioning
confidence: 99%